Longitudinal White Matter Changes following Carbon Monoxide Poisoning: A 9-Month Follow-Up Voxelwise Diffusional Kurtosis Imaging Study - Chou, M.-C.; Li, J.-Y.; Lai, P.-H. (American journal of neuroradiology : AJNR, 2019)
Patients with carbon monoxide (CO) intoxication exhibit progressive WM changes that are not well-understood. The purpose of this study was to detect longitudinal WM changes using voxelwise diffusional kurtosis imaging in patients with CO intoxication from the acute-to-chronic stage after CO intoxication. Twenty-four patients with CO intoxication and 21 age- and sex-matched healthy controls were enrolled in this study. Diffusional kurtosis imaging was performed on all subjects and was conducted repeatedly in patients at 1 week and 1, 3, and 9 months after CO intoxication. Voxelwise diffusional kurtosis imaging analysis was performed to detect global WM changes in the patients with and without WM lesions. Receiver operating characteristic analysis was performed to compare the performance of diffusional indices in differentiating patients with delayed neuropsychiatric sequelae from patients without them. In voxelwise analysis, progressive WM changes were detected in patients with WM lesions. In the acute phase, WM injuries were found mainly in the dopaminergic pathways at 1 week, whereas in the chronic stage, WM injuries extended toward subcortical areas from 1 to 9 months. However, no significant WM change was noted in patients without WM lesions during the 9 months after CO intoxication. Moreover, receiver operating characteristic analysis demonstrated that axial kurtosis and mean kurtosis values had better performance than other diffusional indices in differentiating patients with delayed neuropsychiatric sequelae from patients without them at 1 week after CO intoxication. Voxelwise diffusional kurtosis imaging analysis was helpful to longitudinally investigate WM changes and predict the prognosis of patients after CO intoxication.